Hand-Arm Vibration Exposure Assessment for a Case-Control Study among German Workers - Christian Freitag; Yi Sun; Frank Bochmann; Winfried Eckert; Benjamin Ernst; Uwe Kaulbars; Uwe Nigmann; Christina Samel; Christian van den Berg; Nastaran Raffler (Proceedings, 2023)
In order to analyse the exposure-response relationship between hand–arm-vibration exposure and the risk of musculoskeletal disorders (MSDs) of upper extremities in an epidemiological case-control study, a database was established to provide technical characteristics such as vibration exposure data and its frequency component measured at workplaces. This hand-arm vibration database consists of over 730 technical tools and devices, whereas 422 devices were used for exposure assessment in the epidemiological case-control study. The devices used were divided into a total of 13 device groups: hammers, grinding machines, compactors, screwdrivers and saws were the most frequently used devices.